2019
DOI: 10.1016/j.ccell.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Non-oncogene Addiction to SIRT3 Plays a Critical Role in Lymphomagenesis

Abstract: Highlights d SIRT3 is highly expressed and linked to unfavorable outcome in DLBCL d SIRT3 is required for anaplerotic metabolism in DLBCL by enhancing GDH activity d Loss of Sirt3 impairs lymphomagenesis and prolongs survival of VavP-Bcl2 mice d Selective inhibition of SIRT3 by YC8-02 kills DLBCLs in vitro and in vivo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
122
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(125 citation statements)
references
References 84 publications
3
122
0
Order By: Relevance
“…We found that HK2‐inducible autophagy is “oncogenic” in MM, particularly in myeloma cells in the hypoxic bone marrow microenvironment. In other hematopoietic tumors, such as diffuse large B‐cell lymphoma, autophagy can also act as a tumor suppressor 44 . In contrast, the oncogenic autophagy mechanism is likely to be myeloma specific because, unlike other cancers, myeloma cells are exposed to intense ER stress caused by large amounts of non‐functional monoclonal proteins.…”
Section: Discussionmentioning
confidence: 99%
“…We found that HK2‐inducible autophagy is “oncogenic” in MM, particularly in myeloma cells in the hypoxic bone marrow microenvironment. In other hematopoietic tumors, such as diffuse large B‐cell lymphoma, autophagy can also act as a tumor suppressor 44 . In contrast, the oncogenic autophagy mechanism is likely to be myeloma specific because, unlike other cancers, myeloma cells are exposed to intense ER stress caused by large amounts of non‐functional monoclonal proteins.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT3 can deacetylate IDH2 to increase its activity in promoting carcinogenesis 107 . In diffuse large B cell lymphomas (DLBCLs), SIRT3 was proven to accelerate TCA cycle metabolism via enhancing GDH activity to promote lymphomagenesis 108 . Not surprisingly, SIRT3 has also been found to promote tumor progression in some other cancers.…”
Section: Sirt3 and Human Diseasementioning
confidence: 99%
“…In work reported during the finalization of our study, a commonly used mitochondrial targeting motif (the triphenylphosphonium group) was attached to a SIRT2 inhibitor, to inhibit SIRT3 in the mitochondria rather than SIRT1 and SIRT2 in the nucleus and cytosol, respectively. [58] The chemotypes developed in the present study, however, have a fundamentally different architecture and includes optimization of their selectivity profiles to dial down affinity for SIRT1 and SIRT2. Our design was predicated on the fusion of attributes from mechanism-based class I sirtuin inhibitors with mitochondria-targeting peptides.…”
Section: Resultsmentioning
confidence: 99%